Enhancing Speaking skill With Correct Pronunciation Using Video of Midwifery Students at Muhammadiyah Manado University - Mutiara Dyina Sari Laya (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The goal of this research was to investigate whether conversational videos could improve the speaking skills of midwifery students at Muhammadiyah Manado University. Specifically, the study looked at how videos could help students develop correct rhythm, stress, intonation, and emotion in their pronunciation. The study involved 32 midwifery students at the university and used an experimental technique with pre-tests and post-tests to collect data. To gather data, the researcher used observation and assessed the students' speaking skills before and after watching the videos. The results showed that the conversational videos were effective in improving the students' pronunciation skills. To get the most benefit from the videos, the students first practiced the conversations featured in the videos. Next, they listened to the conversations, repeated them, and then practiced speaking in front of the class. The findings showed that the final good value increased significantly from the pre-test stage to the post-test stage. In the pre-test, the students' good value was 22%, but this increased to 47% in the post-test. Moreover, the lack of value decreased by 19% in the post-test compared to the pre-test.